DIGITAL ECONOMY RESILIENCE: BUSINESS ADAPTATION STRATEGIES IN AN ERA OF MARKET VOLATILITY - Wulandari Wulandari; Nurussama Nurussama (Adisam Publisher, 2025)
Resilience in the digital economy is increasingly crucial amidst high market volatility. This article explores business adaptation strategies in the face of uncertainty through the utilisation of digital technologies. Technology plays an important role in modernising company operations, enabling innovation, and improving customer interactions. The main focus is on strengthening technology infrastructure, utilising data for better decision-making, and developing an adaptive ecosystem. Effective digital transformation enables businesses to turn market challenges into opportunities, strengthen competitiveness, and ensure future sustainability. Finally, digital economic resilience is not only essential for business resilience, but also for gaining competitive advantage in a volatile market environment, emphasising innovation, collaboration and sustainability.